2019
DOI: 10.1088/1361-6560/aafef0
|View full text |Cite
|
Sign up to set email alerts
|

Compatibility of 3D printing materials and printing techniques with PAGAT gel dosimetry

Abstract: Polymer gel (PG) dosimetry enables three dimensional (3D) measurement of complex dose distributions. However, PGs are strongly reactive with oxygen and other contaminations, limiting their applicability by the need to use specific container materials. We investigate different 3D printing materials and printing techniques for their compatibility with PG. Suitable 3D printing materials may provide the possibility to perform PG dosimetry in complex-shaped phantoms. 3D printed and PG-filled test vials were irradia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 23 publications
1
18
0
Order By: Relevance
“…As an example, the new 3D printed prostate organ surrogate could be filled with polymer dosimetry gel instead of tissue surrogate. The compatibility of polymer dosimetry gel with the 3D print material of the prostate has already been demonstrated by Elter et al 27 This combination would allow for additional 3D dose measurements in the target, which was not possible with the ADAM phantom. An upcoming study will further elaborate on this point.…”
Section: E Potential Applications In Image Guided Radiotherapy Plamentioning
confidence: 93%
“…As an example, the new 3D printed prostate organ surrogate could be filled with polymer dosimetry gel instead of tissue surrogate. The compatibility of polymer dosimetry gel with the 3D print material of the prostate has already been demonstrated by Elter et al 27 This combination would allow for additional 3D dose measurements in the target, which was not possible with the ADAM phantom. An upcoming study will further elaborate on this point.…”
Section: E Potential Applications In Image Guided Radiotherapy Plamentioning
confidence: 93%
“…Therefore, all workflows for dosimetry studies are well established at our institution. 7,14,21,22,24…”
Section: Methodsmentioning
confidence: 99%
“…Slight discrepancies (maximum 5%) between measured and planned doses were observed only on the edges of the prostate organ surrogate. These discrepancies could potentially result from the wall effect 21 , on the other hand they appear to have a non-random structure on the gamma maps (Figure 4). Further measurements should be done to investigate this effect.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Especially, it is necessary to carry out the experimental dosimetric verification before radiotherapy treatments, and generally phantoms have been used for the verification because it is difficult to directly measure actual 3D dose distribution at the target volume inside human body. Recent investigations have demonstrated that additive manufacturing enables us to fabricate the desired shape of phantoms (Takeshi et al 2017;Forte et al 2016;Elter et al 2019;Pantelis et al 2018;Leonard et al 2018;Fabian et al 2016). Due to the irradiated regions in polymer gels becoming visibly opaque with absorbed dose, polymer gels have been considered as an alternative to water as material of phantoms.…”
Section: Introductionmentioning
confidence: 99%